(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The rapid development of digital technology has significantly transformed the creative economy sector, particularly through the use of digital platforms that enable the creation and monetization of content on a broad scale. This study aims to analyze the influence of digital content monetization strategies and the utilization of platform-based creative economy ecosystems on the performance of creative economy actors in Semarang City. The research employs a quantitative descriptive approach using a survey method involving 100 respondents who are actively engaged in digital platforms such as YouTube, Instagram, TikTok, and Shopee. The sampling technique applied was purposive sampling, with respondents who have been involved in monetization activities for at least six months.The findings indicate that digital content monetization strategies have a positive and significant effect on monetization success. Likewise, the utilization of digital platforms positively influences the performance of creative economy actors. Simultaneously, both variables contribute to the success of digital content monetization in Semarang City. These results highlight that the combination of creativity, digital business strategies, and technological adaptation serves as the key factor in enhancing the economic value of digital content. Nevertheless, challenges such as limited digital literacy, inadequate understanding of platform algorithms, and fluctuating audience trends remain. Therefore, strengthening digital capabilities and fostering a sustainable creative ecosystem are essential for improving the competitiveness and resilience of creative economy actors in the digital era